2017
DOI: 10.1002/prep.201700040
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐induced Deflagration for the Characterization of Energetic Materials

Abstract: Standard propellant and detonation tests typically performed to characterize the performance of energetic materials require large quantities of material (at least tens of grams) and can be expensive and time-consuming. This work introduces a method for characterizing the deflagration of energetic materials in a laboratory setting, using only 15-20 mg of energetic material. Temperature, energy release and emission signatures were measured and analyzed for the laser-induced deflagration of 8 different convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…S3), neither the Al 2 O 3 nor the Al/I 2 O 5 mixture resulted in significant reaction following the decay of the laser-induced plasma. The combustion of the Al particles ejected into the air above the sample surface was similar to that previously observed during the laser-induced deflagration of energetic materials 7 . Although the Al 2 O 3 and Al/I 2 O 5 residues were not as thick as the micron-sized Al because of the way the material spread on the tape, shots with similar amounts of material removal (~100 μg per shot) could be compared directly to account for the differences in excess material; even with comparable masses of material ejected above the sample surface, of these three samples only the micron-Al sample resulted in late-time combustion emission.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…S3), neither the Al 2 O 3 nor the Al/I 2 O 5 mixture resulted in significant reaction following the decay of the laser-induced plasma. The combustion of the Al particles ejected into the air above the sample surface was similar to that previously observed during the laser-induced deflagration of energetic materials 7 . Although the Al 2 O 3 and Al/I 2 O 5 residues were not as thick as the micron-sized Al because of the way the material spread on the tape, shots with similar amounts of material removal (~100 μg per shot) could be compared directly to account for the differences in excess material; even with comparable masses of material ejected above the sample surface, of these three samples only the micron-Al sample resulted in late-time combustion emission.…”
Section: Resultssupporting
confidence: 83%
“…The laser-induced air shock from energetic materials (LASEM) technique has recently been used to estimate the detonation velocities of novel energetic materials 4,5 and conventional military explosives doped with Al or boron (B) additives 6 . Slower energy release such as that from combustion reactions in air results in strong laser-induced deflagration reactions on the millisecond timescale 7 ; typically, energetic materials such as trinitrotoluene (TNT) that make good propellants have significantly higher deflagration intensities than more powerful military explosives such as RDX that produce faster detonation waves (and thus, faster laser-induced shock velocities). Therefore, TNT is a good baseline explosive to evaluate the performance of metal particle additives that typically enhance late-time blast effects but inhibit detonation velocities.…”
Section: Introductionmentioning
confidence: 99%
“…The emission spectra resulting from the pulsed laser excitation of the energetic materials provide information about the elemental content of the sample (including impurities) [16,17], the chemical reactions in the laser-induced plasma [11,13,14,18], and any combustion reactions that occur after the plasma is gone (millisecond timescale) [13][14][15]. Similar emission features were observed in the b-CL-20, e-CL-20, RSI-007 baseline, and two aged RSI-007 samples ( Figure 1); no emission features from non-organic impurities or the binder materials were detectable.…”
Section: Emission Spectramentioning
confidence: 60%
“…Despite the fact that all the CL-20 in the individual piles appeared to react following laser excitation, the emission spectra show that more combustion occurred for the thin residue samples (indicated by the stronger CN, CaOH, Na, and K emission). Previous studies have shown that the material that is ejected off the sample slide by the laser-induced shock wave into the air heated by the plasma and the passage of the shock wave combusts on the millisecond timescale [7,15]. This suggests that the material in the piles of CL-20 reacted on the microsecond timescale, which could affect the measured laser-induced shock wave velocities (since more material would lead to additional exothermic reactions in the plasma, increasing the plasma temperature and accelerating the shock wave).…”
Section: Emission Spectramentioning
confidence: 65%
See 1 more Smart Citation